A Simple Tactic for Purchasing French Oak Barrels - Quintanar, Sarah; Sims, Eric; Terry, Andy (Journal of Applied Business and Economics, 2018)
This paper identifies a cost-minimizing tactic for U.S. wineries when buying French oak barrels. An otherwise trivial decision is potentially confounded by wineries’ order timing choice and exchange rate risk. Using an intuitive model, which applies exchange rate futures prices and sixteen years of price data for a specific custom-made French oak barrel, we provide a general decision rule. The simple strategy of taking the early order discount dominates all alternative strategies and would have saved wineries nearly $78,000 compared to the more traditional ordering timeframe. Interestingly, using futures market prices does not improve the cost savings. “In wine, there’s truth.” Pliny the Elder, Natural History Neither do men pour new wine into old wineskins. If they do, the skins will burst, the wine will spill, and the wineskins will be ruined. Instead, they pour new wine into new wineskins, and both are preserved." Matthew,9:17.